The effects of soil pollution and its relation with morbidity in shoreline areas - Lourenço, Roberto Wagner [UNESP]; Monteiro, Sandra Regina [UNESP]; Roveda, Masalskiene [UNESP]; Rosa, Andre Henrique [UNESP]; Fraceto, Leonardo Fernandes [UNESP]; Ferreira, Beatriz Antunes Justo [UNESP]; Donalisio, Maria Rita; Cordeiro, Ricardo (My University, 2011)
Soil is a basic resource representing a fundamental component of ecosystems and natural cycles, a water reservoir, an essential yield for agriculture and further human and animal activities. Soil and subsoil pollution is not only significant in terms of environmental loss, but also a matter of environmental and public health. Solid, liquid and gaseous residues are the major soil contamination agents. They provide from urban conglomerates and industrial areas in which it is possible to emphasize the chemical, petrochemical and textile industry; thermoelectric, mining, and ironmaster activities. The contamination process can thus be defined as compound addition to soil, from what qualitative and or quantitative manners can modify soil natural characteristic and use, producing baneful and deteriorative effects on human health. Studies has shown that human exposition to high concentration of some heavy metals found on soil can cause serious health problems, such as pulmonary or kidney complications, liver and nervous system harm, allergy, and the chronic exposition leads to death. The present study searches for the correlation among soil contamination, done through geochemical baseline survey of a representative industrial contamination area in the shoreline of Sao Paulo state, and verifies if lead, cadmium and mercury concentration exhibit correlation with morbidity rates. On behalf of that, the study will be conducted by spatial analysis using Geographical Information Systems for mapping and data handle. The used data are samples of concentration of heavy metals Cd, Pb and Hg. They were sampled and spatial distributed by geostatistics methods, along with the area morbidity data available from the Info Department of the Brazilian Health System (DATASUS) georeferenced by neighborhood. In order to verify if there is a relation between heavy metals soil pollution and morbidity records spatial distribution, a thematic mapping procedure will be executed with the involved variables. Spatial correlation and regression analysis will be done in addition, using the morbidity registers as the dependable variables and heavy metal variation as the independent variables. It is expected, by the end of the study, to identify the human health potential risk areas, moreover to be able to provide assistance in terms of new methodologies that could facilitate soil pollution control programs and public health planning.